RESTRICTIVE VERSUS LIBERAL BLOOD TRANSFUSION FOR ACUTE UPPER GASTROINTESTINAL BLEEDING (TRIGGER): PRAGMATIC, CLUSTER RANDOMISED, FEASIBILITY TRIAL. Issue 9 (14th August 2014) - Gray, A; Jairath, V; Kahan, B; Dore, C; Palmer, K; Travis, S; Logan, R; Walsh, T; Murphy, M
Abstract : Objectives & Background: Transfusion thresholds for upper gastrointestinal bleeding (UGIB) are controversial. Observational studies suggest associations between liberal red blood cell (RBC) transfusion and adverse outcome. A recent trial reported increased mortality following liberal transfusion. We delivered a cluster randomised trial to evaluate the feasibility and safety of implementing a restrictive (transfusion when haemoglobin (Hb) <8 g dL) vs liberal (transfusion when Hb <10 g/dL) RBC transfusion policy for UGIB. Methods: Hospitals were randomised to a policy which was implemented through a multi-faceted educational intervention. Patients were recruited in Emergency Departments and acute admission units. All adult patients were eligible to participate, regardless of co-morbidity; the only exclusion criterion was exsanguinating haemorrhage. Feasibility and exploratory clinical outcomes were recorded up to day 28. Results: 936 patients were enrolled in six hospitals. Rockall and Blatchford risk scores were identical between policies. Protocol adherence was 96% in the restrictive policy vs 83% in the liberal policy (difference 14%, 95% CI 7 to 21%). In patients with Hb <120 g/L, Hb at discharge was lower for the restrictive policy (difference −0.7; 95% CI −1.4 to 0.0; p=0.05). For the restrictive policy fewer patients received RBCs (difference −13%, 95% CI −35 to 11%) with on average 0.8 (−1.9 to 0.3) fewer RBC units transfused. Clinical outcomes were better in the restrictive policy: 28-day further bleeding, 5% restrictive vs 9% liberal (difference −3.7%, 95% CI -12.2 to 4.8%); 28-day mortality, 5% restrictive vs 7% liberal (difference −1.3%, 95% CI −8.0 to 5.5%).; serious adverse events, 18% restrictive vs 22% liberal (difference −4.9%, 95% CI −22.6 to 12.8%). In the subgroup with IHD, there was a large observed difference for mortality (12% restrictive arm (n=6) vs. 3% liberal arm (n=2); interaction P=0.11). Conclusion: Adherence to both policies was high, resulting in a reduction in RBC transfusion and separation in the degree of anaemia and RBC exposure. There was a trend towards improved safety in the restrictive policy. We have demonstrated that a large-scale cluster randomised trial is feasible and is now warranted to determine the effectiveness of implementing restrictive RBC transfusion for all patients with AUGIB.